Effects of Ultrasound on Zinc Oxide/Vermiculite/Chlorhexidine Nanocomposite Preparation and Their Antibacterial Activity - Čech Barabaszová, Karla; Holešová, Sylva; Šulcová, Kateřina; Hundáková, Marianna; Thomasová, Barbora (Nanomaterials (Basel, Switzerland), 2019)
Microbial infection and biofilm formation are both problems associated with medical implants and devices. In recent years, hybrid organic-inorganic nanocomposites based on clay minerals have attracted significant attention due to their application potential in the field of antimicrobial materials. Organic drug/metal oxide hybrids exhibit improved antimicrobial activity, and intercalating the above materials into the interlayer of clay endows a long-term and controlled-release behavior. Since antimicrobial activity is strongly related to the structure of the material, ultrasonic treatment appears to be a suitable method for the synthesis of these materials as it can well control particle size distribution and morphology. This study aims to prepare novel, structurally stable, and highly antimicrobial nanocomposites based on zinc oxide/vermiculite/chlorhexidine. The influence of ultrasonic treatment at different time intervals and under different intercalation conditions (ultrasonic action in a breaker or in a Roset's vessel) on the structure, morphology, and particle size of prepared hybrid nanocomposite materials was evaluated by the following methods: scanning electron microscopy, X-ray diffraction, energy dispersive X-ray fluorescence spectroscopy, carbon phase analysis, Fourier transforms infrared spectroscopy, specific surface area measurement, particle size analysis, and Zeta potential analysis. Particle size analyses confirmed that the ultrasonic method contributes to the reduction of particle size, and to their homogenization/arrangement. Further, X-ray diffraction analysis confirmed that ultrasound intercalation in a beaker helps to more efficiently intercalate chlorhexidine dihydrochloride (CH) into the vermiculite interlayer space, while a Roset's vessel contributed to the attachment of the CH molecules to the vermiculite surface. The antibacterial activity of hybrid nanocomposite materials was investigated on Gram negative (Escherichia coli, Pseudomonas aeruginosa) and Gram positive (Staphylococcus aureus, Enterococcus faecalis) bacterial strains by finding the minimum inhibitory concentration. All hybrid nanocomposite materials prepared by ultrasound methods showed high antimicrobial activity after 30 min, with a long-lasting effect and without being affected by the concentration of the antibacterial components zinc oxide (ZnO) and CH. The benefits of the samples prepared by ultrasonic methods are the rapid onset of an antimicrobial effect and its long-term duration.
Keywords: vermiculite; ultrasonic intercalation; zinc oxide nanoparticles; chlorhexidine; mechanical stirring; antibacterial activity